Ketone bodies and exercise performance: The next magic bullet or merely hype? - Pinckaers, P. J. M.; Churchward-Venne, T. A.; Bailey, D.; van Loon, L. J. C. (Sports Medicine, 2017)
Elite athletes and coaches are in a constant search for training methods and nutritional strategies to support training and recovery efforts that may ultimately maximize athletes` performance. Recently, there has been a re-emerging interest in the role of ketone bodies in exercise metabolism, with considerable media speculation about ketone body supplements being routinely used by professional cyclists. Ketone bodies can serve as an important energy substrate under certain conditions, such as starvation, and can modulate carbohydrate and lipid metabolism. Dietary strategies to increase endogenous ketone body availability (i.e., a ketogenic diet) require a diet high in lipids and low in carbohydrates for ~4 days to induce nutritional ketosis. However, a high fat, low carbohydrate ketogenic diet may impair exercise performance via reducing the capacity to utilize carbohydrate, which forms a key fuel source for skeletal muscle during intense endurance-type exercise. Recently, ketone body supplements (ketone salts and esters) have emerged and may be used to rapidly increase ketone body availability, without the need to first adapt to a ketogenic diet. However, the extent to which ketone bodies regulate skeletal muscle bioenergetics and substrate metabolism during prolonged endurance-type exercise of varying intensity and duration remains unknown. Therefore, at present there are no data available to suggest that ingestion of ketone bodies during exercise improves athletes` performance under conditions where evidence-based nutritional strategies are applied appropriately.